ACOUSTIC DETECTION AND CHARACTERIZATION OF MARINE SEDIMENT WITH SHALLOW SEISMIC TECHNOLOGY IN RAMBAT WATERS, BANGKA BELITUNG - Haqqu Ramdhani; Henry M. Manik; Susilohadi Susilohadi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
High resolution of marine seismic reflection seismic were used to detect the layers of seafloor sediment and to interpret the seismic data geologically. The objectives of this study weres to detect and to characterize the seafloor sediment in the Rambat area, West Bangka, Bangka Belitung. Acquisition data was held on 10-24  August  2012 located between 105.1°00'00" - 105.5°00'00 " N and 1.7°00'00"-1.9° 00'00" W. Several methods used to process the data were geometry processing, band pass filter, predictive deconvolution,  and Autocoralation Gain Control (AGC)  in order to reduce the multiple noise and to  ease the data interpretation. Seismic cross section found in Cross Rambat (CRMBT) line 11 exhibited  sedimentation process of the sea floor which rocky substrates. The process was assumed to be occurred due to legal and illegal mining activities for long period of time. Keywords: seismic, acoustic, sediment, band pass filter, deconvolution, noise